New Results on the Canonical Structure of Classical Non-Linear Sigma Models (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
The material presented here is based on recent work of the author (done in collaboration with colleagues from the University of Freiburg and from the University of Sao Paulo) which has produced new insight into the algebraic structure of classical non-linear sigma models as (infinite-dimensional) Hamiltonian systems [1-5].